The Effect of the Inquiry Learning Model on Scientific Literacy and Critical Thinking Skills of Fifth-Grade Students at SDN Sukadanau 04 - Putri Syafira; Awalina Barokah (Darul Yasin Al Sys, 2026)
Scientific literacy and critical thinking skills are essential competencies for students in responding to the demands of twenty-first-century education. However, various assessments indicate that Indonesian students’ scientific literacy remains relatively low, underscoring the need for instructional models that actively engage learners in inquiry-based knowledge construction. This study aimed to examine the effect of the Inquiry Learning model on the scientific literacy and critical thinking skills of fifth-grade students at SDN Sukadanau 04. A quantitative approach with a quasi-experimental non-equivalent control group design was employed. The sample consisted of 60 students divided into experimental and control groups. Data were collected through observation, interviews, tests, and documentation, and were analyzed using normality tests, homogeneity tests, independent sample t-tests, and regression analysis. The findings revealed that the Inquiry Learning model had a positive and significant effect on students’ scientific literacy and critical thinking skills. The independent sample t-test showed a significance value of 0.000 (p < 0.05), while regression analysis produced an R² value of 0.707, indicating that the model substantially explained improvements in the measured competencies. These findings demonstrate that Inquiry Learning is more effective than conventional instruction in enhancing scientific literacy and critical thinking skills among elementary school students. The study contributes to science education by providing empirical evidence on the effectiveness of Inquiry Learning as an alternative instructional model for fostering twenty-first-century competencies in elementary education.